Near-infrared spectra for the AfSIS Sentinel Sites in Tanzania - Winowiecki, Leigh Ann; Morrison, Scholastica; Weullow, Elvis; Sila, Andrew M.; Vågen, Tor-Gunnar (2015)
The Africa Soil Information Service (AfSIS), was a project led by the Tropical Soil Biology and Fertility Institute (TSBF) of the International Center for Tropical Agriculture (CIAT), based in Nairobi, in collaboration with several partners including the World Agroforestry Centre (ICRAF). The AfSIS projectf aimed to narrow sub-Saharan Africa s (SSA) soil information gap and provide a consistent baseline for monitoring soil ecosystem services. Sentinel sites were established and top- and subsoil samples were collected from each subplot at 0-20 cm and 20-50 cm depth increments, respectively, and pooled (composited) into one sample for each plot and depth, resulting in a total of 320 standard soil samples per sentinel site (Vågen et al., 2010). These samples were analyzed using near-infrared (NIR) spectroscopy. NIR spectral measurements were conducted through regional laboratories in eastern, southern and West Africa (Vågen et al., 2010). The NIR spectral laboratory network used standard instrumentation and standard operating procedures to ensure reproducibility of results among laboratories and over time (Vågen et al., 2010). The ICRAF laboratory provided technical backstopping and quality control for the network of NIR spectral laboratories. This is the complete dataset of the NIR spectra matched with the Sentinel Site sample details for all seven AfSIS sentinel sites sampled and analyzed in Tanzania in 2010.Reference:Vågen, T-G., Shepherd, K., Walsh, M., Winowiecki, L., Desta, L. and Tondoh, J. 2010. Soil health surveillance: Technical specifications. World Agroforestry Centre (ICRAF). Nairobi, Kenya.